2018
DOI: 10.5194/nhess-18-2675-2018
|View full text |Cite
|
Sign up to set email alerts
|

Implementation and validation of a new operational wave forecasting system of the Mediterranean Monitoring and Forecasting Centre in the framework of the Copernicus Marine Environment Monitoring Service

Abstract: Abstract. Within the framework of the Copernicus Marine Environment Monitoring Service (CMEMS), an operational wave forecasting system for the Mediterranean Sea has been implemented by the Hellenic Centre for Marine Research (HCMR) and evaluated through a series of preoperational tests and subsequently for 1 full year of simulations (2014). The system is based on the WAM model and it has been developed as a nested sequence of two computational grids to ensure that occasional remote swell propagating from the N… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 47 publications
(65 reference statements)
5
17
0
Order By: Relevance
“…The results presented in Section 3 show that the operational wave system performs better in deep waters and intermediate waters than in the nearshore. This outcome is in agreement with Ravdas et al [10] who found relatively low correlations at coastal locations. Whereas correlation coefficients for wind speed and significant wave height are 0.91 and 0.93 in deep waters at the Lion buoy site, they drop to 0.62 and 0.85 when computed data are compared with measurements in the nearshore at Poetto beach.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The results presented in Section 3 show that the operational wave system performs better in deep waters and intermediate waters than in the nearshore. This outcome is in agreement with Ravdas et al [10] who found relatively low correlations at coastal locations. Whereas correlation coefficients for wind speed and significant wave height are 0.91 and 0.93 in deep waters at the Lion buoy site, they drop to 0.62 and 0.85 when computed data are compared with measurements in the nearshore at Poetto beach.…”
Section: Discussionsupporting
confidence: 93%
“…Under the same lead-time range, the relative error passes from 17 to 28% at La Revellata buoy and from 28 to 35% at Poetto beach. This deterioration of the wave forecast accuracy with the lead-time is likely to be related to larger uncertainties in the wind forcing fields [10,37]. Despite the accuracy loss, the relative error remains under moderate values, confirming the reliability of the prediction for the time window covered by the simulation.…”
Section: Operational Wave Systemmentioning
confidence: 76%
See 1 more Smart Citation
“…At the regional level, the impact of assimilating satellite observations on the Med-Wave system has been evaluated considering the Med-Waves-V4 system, assimilating along-track significant wave height observations from Jason-2 and Saral satellites at 3-hourly intervals, vs. the Med-Waves-V3.2 system without data assimilation (Ravdas et al, 2018). Data assimilation improves results along satellite tracks, as well as at the great majority of the wave buoy locations.…”
Section: Wavesmentioning
confidence: 99%
“…In addition, the computation of the bottom stress of the ocean models (respectively, ROMS and ADCIRC) was updated in order to consider the spatial distribution of the sediment grain size at the bottom of the Adriatic Sea, extracted from the Adriatic Seabed database [40], and the wave effects. To reproduce the storm as accurately as possible, the basic module was set up to run for three days between 27 October and 30 October 2018, with initial conditions and boundary forcing provided by (1) the 6 hourly ERA-Interim reanalysis fields [41], (2) the daily analysis MEDSEA-Ocean fields [42], and (3) the hourly MEDSEA-Wave fields [43]. The nearshore module, forced by the results of the basic module, was set up to run between midday on 28 and 30 October 2018.…”
Section: Wave Modelingmentioning
confidence: 99%